Macular hole retinal detachment in extensive myelinated retinal nerve fiber and high myopia with Straatsma syndrome: A case report - Ayumi Usui-Ouchi; Nobuyuki Ebihara; Shintaro Nakao (American Journal of Ophthalmology Case Reports, 2024)
Purpose: We present a case of macular hole retinal detachment (MHRD) in a patient with Straatsma syndrome, a rare condition characterized by extensive unilateral myelinated retinal nerve fibers (MRNF), high myopia, and amblyopia. This study aimed to highlight the clinical presentations, diagnostic challenges, and success of surgical interventions. Observation: A 32-year-old Asian woman with a history of high myopia and poorly corrected vision in her right eye since childhood presented with a sudden loss of vision in the right eye. Examination revealed extensive MRNF and retinal detachment with a macular hole. A standard three-port pars plana vitrectomy was performed, and tight vitreous retinal adhesions were observed. PFCL-assisted inverted internal limiting membrane (ILM) flap technique was performed. Silicone oil was used owing to its tight vitreous retinal adhesion. Postoperatively, the macular hole was closed, the retina was reattached, and partial disappearance of the MRNF was observed. Conclusion and importance: This case report describes a successful surgical intervention for MHRD associated with Straatsma syndrome. The PFCL-assisted inverted ILM flap technique is effective for managing complicated cases of MHRD. The partial disappearance of MRNF after vitrectomy suggests potential nerve fiber layer damage, possibly due to retinal detachment or the use of silicone oil. This case highlights the unique features of MHRD, a rare disease associated with Straatsma syndrome.